Echinomycin binding to alternating AT. - Fox, K R (1991)
We have studied the binding of echinomycin to DNA fragments containing GC-rich regions flanked by blocks of alternating AT by DNase I footprinting and diethylpyrocarbonate modification. Regions of alternating AT flanking the sequences CCCG, CCGC, CGGC and GG show a four base pair DNase I cleavage pattern and reaction of alternate adenines with diethylpyrocarbonate. This pattern is strongest when the AT-block is immediately adjacent to the CpG ligand binding site. We explain these phenomena by suggesting that echinomycin binds to the dinucleotide step ApT in a cooperative fashion. The cooperative effects can be transmitted through the dinucleotide step GC but not CC or AA. No such repetitive patterns are seen with surrounding regions of (ATT).(AAT). Evidence is presented for secondary drug binding sites at CpC and TpG with weaker interaction at the CpG site within the hexanucleotide TTCGAA.